2007
DOI: 10.1002/ange.200702560
|View full text |Cite
|
Sign up to set email alerts
|

Desaktivierung von Ruthenium‐Metathesekatalysatoren durch intramolekulare Carben‐Aren‐Verknüpfung

Abstract: Sauerstoff macht inaktiv: Metathesekatalysatoren mit sterisch ungehinderten ortho‐Positionen im N‐Aryl‐Substituenten können durch C‐H‐Aktivierung zu inaktiven Ruthenium‐Komplexen führen. Der Prozess verläuft vermutlich über eine pericyclische Reaktion und wird durch Sauerstoff irreversibel (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
7

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 32 publications
0
10
0
7
Order By: Relevance
“…Initiators 2, 3, and 4 have been prepared as described earlier. [30,54] The synthetic protocol used there was also applied to the synthesis of initiator 1 (Scheme 1, PCy 3 = tricyclohexylphosphine). This compound was prepared by means of a Pd-catalyzed N-arylation reaction of N-benzyl-N-(2-aminoethyl)amine with bromomesitylene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initiators 2, 3, and 4 have been prepared as described earlier. [30,54] The synthetic protocol used there was also applied to the synthesis of initiator 1 (Scheme 1, PCy 3 = tricyclohexylphosphine). This compound was prepared by means of a Pd-catalyzed N-arylation reaction of N-benzyl-N-(2-aminoethyl)amine with bromomesitylene.…”
Section: Resultsmentioning
confidence: 99%
“…(2), [54] [RuCl 2 (1-mesityl-3-methylimidazolin-2- (3) is described elsewhere. [30] N-Benzyl-N'-(2,4,6-trimethylphenyl)ethane-1,2-diamine: 3 ] (dba = dibenzylideneacetone; 1.0 mol %), (AE )-BINAP (BINAP = 2,2'bis-(diphenylphosphino)-1,1'-binaphthyl; 3.0 mol %), and toluene (25 mL) were mixed together.…”
Section: Molecular Weights Were Determined By Calibration Vs Polya C mentioning
confidence: 99%
“…This was seen as evidence for p-p interactions [46] between an aromatic ring at the NHC ligand and the Ru-benzylidene unit. In the meantime, it was shown that even in Grubbs II-type complexes with mixed aryl, alkyl-NHC [40,[47][48][49][50] or related ligands [49] the aryl groups are located above the benzylidene unit and the alkyl group above the empty coordination site. For bulky alkyl groups steric arguments account for the observed orientation of the N-substituents.…”
Section: Introductionmentioning
confidence: 98%
“…The metal coordination environment is no longer a square-pyramid, but rather a distorted octahedron. [9] As a result of twist there is a strong steric interaction between the ligand and chlorine atom Cl1. The Ru À Cl bond lengths of 2.350(3) are significantly shortened and the Cl1-Ru1-Cl2 bond angle of 158.57(6)8 is increased.…”
mentioning
confidence: 99%